2007
DOI: 10.1177/003804070708000302
|View full text |Cite
|
Sign up to set email alerts
|

Staying Back and Dropping Out: The Relationship Between Grade Retention and School Dropout

Abstract: Students who repeat a grade prior to high school have a higher risk of dropping out of high school than do students who are continuously promoted. This study tested whether standard theories of dropout—including the participation-identification model and the social capital model—explain this link. Although the presence of variables, including academic achievement and disciplinary problems, reduces the higher probability of retained students dropping out, existing models of dropping out do not adequately explai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
70
0
9

Year Published

2009
2009
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 111 publications
(84 citation statements)
references
References 60 publications
5
70
0
9
Order By: Relevance
“…In addition, one of the most powerful predictors of dropping out of school is student retention in grade. Students who have been retained are two to eleven times more likely than their peers to drop out of high school (Jimerson, Whipple, Anderson, & Dalton, 2002;Stearns, Moller, Blau, & Potochnick, 2007). …”
Section: Background and Purposementioning
confidence: 99%
“…In addition, one of the most powerful predictors of dropping out of school is student retention in grade. Students who have been retained are two to eleven times more likely than their peers to drop out of high school (Jimerson, Whipple, Anderson, & Dalton, 2002;Stearns, Moller, Blau, & Potochnick, 2007). …”
Section: Background and Purposementioning
confidence: 99%
“…Empirical studies with Mexican American and Latino samples have demonstrated that family SES was a significant predictor of youth's academic outcomes, including test scores (Morales & Saenz, 2007), grade point average (GPA; Portes & Rumbaut, 2001) and school drop out (Stearns, Moller, Blau, & Potochnick, 2007). However, these studies examined the effect of a single SES factor that was either a composite of multiple indicators or a single measure of SES.…”
Section: Ses and Academic Outcomes Of Mexican American Youthsmentioning
confidence: 99%
“…The data collected replicated results identified in previous studies that extend past the national and large urban district findings: retaining a child increased the likelihood of high school dropout or withdrawal (Bowers, 2010;Roderick, 1994;Stearns, Moller, Potochnick, & Blau, 2007). Bowers (2010) study transformed the results into hazard probability to assess risk and found that retained students were 91.1% more likely to drop out of high school.…”
Section: Grade Repetition Determinantssupporting
confidence: 71%